2015
DOI: 10.1515/ppb-2015-0004
|View full text |Cite
|
Sign up to set email alerts
|

Decisional procrastination of school-to-work transition: Personality correlates of career indecision

Abstract: Procrastination as putting off until tomorrow what one had intended to do today is well-known tendency in everyday life. In an attempt to understand the character of procrastination in different life-domains, a large body of research has been accumulated over the last decades. This article was aimed to evaluate a specific decisional procrastination of school-to-work transition (SWT) that is treated as maturity postponement. Two studies are reported examining SWT procrastination defined as career indecision amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 34 publications
3
10
0
2
Order By: Relevance
“…Research results have shown that decision-making difficulty leads to academic procrastination (Eerde, 2003;Uzun Özer, 2009). It is also noted that individuals who show academic procrastination also delay decision making (Bańka & Hauziński, 2015;Ferrari et al, 1995;Ferrari, Crum, & Pardo, 2018). As stated by previous research results, there is a connection between decision-making styles and procrastination (Balkıs, 2007;Uğurlu, 2013).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Research results have shown that decision-making difficulty leads to academic procrastination (Eerde, 2003;Uzun Özer, 2009). It is also noted that individuals who show academic procrastination also delay decision making (Bańka & Hauziński, 2015;Ferrari et al, 1995;Ferrari, Crum, & Pardo, 2018). As stated by previous research results, there is a connection between decision-making styles and procrastination (Balkıs, 2007;Uğurlu, 2013).…”
Section: Introductionmentioning
confidence: 84%
“…Studies show that indecisive individuals exhibit defensive and avoidant approaches and, therefore, procrastinate (Deveci, 2011;Gati, Krausz & Osipow, 1996). In studies that address indecision and procrastination together, it has been shown that these two concepts are strongly correlated (Bańka & Hauziński, 2015;Lauderdale, 2017;Lauderdale, Martin, & Moore 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The first one as developmental procrastination is a rational path that prepares for a new equilibrium and driving force; however, the second one is a destructive form of petrification -negative pathological identity in doing nothing a . A partial analogy takes place here with functional and dysfunctional procrastination with one important difference -despite procrastination correlating with certain personality traits (Millgram, Tenne, 2000;Bańka, Hauziński 2014), contrary to indecisiveness it is never a personality trait in itself. Indecisiveness as a pathological trait and personality (Rassin, et al 2007) permanently prevents making tough decisions by an individual in challenging life aspects like business, work, educa-tion, accommodation or marriage regardless whether an individual is under considerable stress or not.…”
Section: Procrastination and Indecisiveness: New Patterns Of Driving mentioning
confidence: 99%
“…Daha sonra Milgram ve Tenne (2000) söz konusu prokrastinasyon çeşitlerini davranışsal ve kararsal prokrastinasyon olmak üzere ikiye indirgemişlerdir (Ilyin, 2011;Klimova, 2014: 288;Kovylin, 2013: 27). Davranışsal prokrastinasyon gerçekleştirilmesi gereken/beklenen faaliyet/görevlerin ertelenmesini ifade ederken, kararsal prokrastinasyon belirli faaliyet/görevlerin gerçekleştirilip gerçekleştirilmeyeceğine dair karar alma süreçlerini ertelemeyi açıklar (Bańka & Hauziński, 2015;Fernie vd., 2009;Sadykova, 2016).…”
Section: İşyeri Prokrastinasyonu / İşyerinde Erteleme Alışkanlığıunclassified